Fine needle aspiration of thyroid nodules in the pediatric population: A 12‐year cyto‐histological correlation experience at north shore‐long island jewish health system. Issue 8 (26th February 2015) - Lale, Seema A.; Morgenstern, Nora N.; Chiara, Sugrue; Wasserman, Patricia
<x xml:space="preserve">Abstract</x> Background Diagnostic evaluation of thyroid nodules by FNA is used in the clinical management triage based on the knowledge of the rate of malignancy of each diagnostic category. The Bethesda System for Reporting Thyroid Cytopathology was published in 2007 by the National Cancer Institute (NCI). Using this classification, we studied our institution's experience in the pediatric population calculating the rate of malignancy for each diagnostic category, comparing our findings to our general patient population and that of the literature. Methods 13, 312 thyroid FNAs were performed at our institution between 1998 and 2010. 282 cases were from patients under 19 years of age. We reviewed and reclassified these cases using the new NCI categories, and pursued cytology‐surgical follow‐up. Results Of the 282 FNA cases, 20.92% (59) were classified as unsatisfactory (U), 48.22, % (136) benign (B), 2.12% (6) Atypia of undetermined significance (AUS), 14.18% (40) suspicious for follicular neoplasm (FN), 2.12% (6) suspicious for malignancy (SM) and 12.41% (35) positive for malignancy (P). The U‐category was further classified into nondiagnostic (ND) 12.41% (35) and cysts (C) 8.51% (24). Seventy‐four children had surgical follow‐up. The rates of histologically confirmed malignancy were 10% in U (1/10), 0% in B (0/17), 50% in AUS (2/4), 39% in FN (7/18), 100% in SM (4/4) and 100% in P (24/24) categories respectively. Among the U category, malignancy rate was 0% for the ND category and 25% for the C category. Conclusions To our knowledge, this is the first study to apply the NCI categories to the pediatric population. The rate of malignancy in the U category was only seen in the specimens with cystic component. AUS and FN categories had a higher malignancy rate (50 and 39% respectively) as compared with that of the general population (15 and 30% respectively). Given that the rates of malignancy are higher for cysts and AUS, the literature recommendation to "follow‐up and repeat" may not apply to the pediatric population. Surgery may be reasonable in these categories instead. Diagn. Cytopathol. 2015;43:598‐604. © 2015 Wiley Periodicals, Inc.